2023
DOI: 10.1177/00111287231180126
|View full text |Cite
|
Sign up to set email alerts
|

Who Commits Terrorism Alone? Comparing the Biographical Backgrounds and Radicalization Dynamics of Lone-Actor and Group-Based Terrorists

Abstract: Why does one person radicalize to involvement in terrorist violence within a group-based context, while another engages in this form of violence alone? Existing research remains subject to limitations related to sample size, ideological and geographical range, and contradictory findings. This article draws on a newly-developed dataset to compare group-based and lone-actor terrorists across a range of predictors. Statistically significant bivariate associations and regression analyses suggest that lone actors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…In comparison, 55% of lone dyads and 65% of group actors had no previous convictions. Further analysis found no significant differences between attacker groups in terms of convicted history and prior convicted violent history, which contrasts with the recent comparative study by Schuurman and Carthy (2023), in which lone actors were found to have fewer criminal antecedents than group actors.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In comparison, 55% of lone dyads and 65% of group actors had no previous convictions. Further analysis found no significant differences between attacker groups in terms of convicted history and prior convicted violent history, which contrasts with the recent comparative study by Schuurman and Carthy (2023), in which lone actors were found to have fewer criminal antecedents than group actors.…”
Section: Resultscontrasting
confidence: 99%
“…In such comparisons, lone actors have been found to be more likely to be older, single, unemployed, with higher educational attainment, or poorer financial status (see Gill et al, 2014, 2021; Horgan et al, 2016). Most recently, Schuurman and Carthy (2023) compared 58 group-based and 45 lone-actor terrorists from across North America and Europe. Lone actors had fewer criminal antecedents, poorer social skills, had typically radicalized at a later age, and had lower exposure to environments enabling group-based participation in terrorism.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we have worked from the assumption that while the predictors of involvement in jihadism and right-wing extremist terrorism are unlikely to be the same, they are likely to be similar enough to warrant both types of individuals being included in our dataset. Similarly, while lone actors do show distinctiveness on a number of predictors, perhaps especially so with regard to higher rates of diagnosed mental illness [24,118], such unique attributes appear to be outweighed by similarities with their group-based counterparts [119][120][121]. Hence, we argue that it makes sense to include both lone actors and group-based extremists in our work.…”
Section: Samplingmentioning
confidence: 85%